Agro-Business of Cashew Nuts in Casamance (Senegal): Strengths, Constraints and Industrialisation Prospects - Mbade, Sene Abdourahmane (European Scientific Journal, ESJ, 2019)
This paper deals with the problem of cashew nuts agro-business in Casamance, Senegal. The internationalization of the marketing of this commodity in virtually all African producing countries gives it an increasingly important place. The methodology is based on a literature review and field surveys, followed by the research conducted using the mapping and data processing software. Low production is due essentially to the nature of the farms which are traditional, family-owned smallholdings. The cashew nut trade is becoming international, with the involvement of foreign actors, especially Indians. The establishment of Indian exporters in the city of Ziguinchor has led to a rapid price escalation due to an upsurge in demand, boosted job creation and increased the city's tax revenues. Ziguinchor has thus become the hub for the flows of the product and people in the sub-region. Industrial processing is faced with a number of challenges, relating especially to the inadequacy of commodity supply and the obsolescence of the equipment. The main recommendation calls for greater State involvement in order to regulate the market and strengthen the financial capacities of processors to ensure the successful industrialization of the product.